Evaluation of Tumour Markers In Our Clinical Environment - Aziz, Amjad; Khan, Sher Muhammad; Nawab, Gul; Ahmad, Iftikhar (Journal of Postgraduate Medical Institute, 2011)
Evaluation of tumour markers was done in 242 patients of various malignancies at different stages and phases of treatment. The evaluation was done in randomly selected cases. Five tumour markers were evaluated namely, Carcinoembryonic Antigens (CEA), Alpha Feto Protein (AFP), CA 125, Prostatic Acid Phosphate (PAP) and Human Chorionic Gonadotrophin (HCG). Titres of PAP were raised in patients with carcinoma of prostate while all other tunours markers showed varied positive results ranging from varied with other tumours marker I different malignancies.